Efficacy of gamma knife radiosurgery for the treatment of trigeminal neuralgia - Filipović, Jelena R; Hajdarpašić, Lejla M; Ćosić, Ana; Zidverc Trajković, Jasna (Medicinski podmladak, 2018)
Introduction: Trigeminal neuralgia, also called “tic douloureux”, is a chronic pain condition that affects the trigeminal nerve and it is most common cause of facial pain in adults. Gamma knife radiosurgery has been increasingly used in the treatment of medically refractory trigeminal neuralgia, as a non-invasive alternative to microvascular decompression and rhizotomies. The Aim: The aim of this study was to determine the early efficacy of gamma knife radiosurgery in a group of patients with trigeminal neuralgia, treated in the Clinical Center of Serbia. Material and Methods: We checked all the patients treated with gamma knife radiosurgery for trigeminal neuralgia at the Clinic of Neurosurgery at the Clinical Center of Serbia in Belgrade, in a period between the end of 2015 and beggining of 2018. They were examined after the first, third, sixth, ninth month and a year after the radiosurgery. Informations about the pain and its intensity, type and dosage of pharmacotherapy were collected. Surgery was considered successful if it reduced the pain for a minimum of 30% or led to the reduction od pharmacotherapy needed to control the pain in comparison to the dosages before surgery. Results: There was a trend of decreased efficacy that lasted for a year after the implementation of procedure, which, most likely, resulted from a short period of monitoring and assessment of the patients condition. Conclusion: The results from this study show that gamma knife radiosurgery could be one of the options in treatment of trigeminal neuralgia. Keywords: trigeminal neuralgia; gamma knife; radiosurgery